Retrospective study on the toxicity induced by stereotactic body radiotherapy: overview of the reunion experience on prostate cancer in elderly patients - Slama, Youssef; Baumont, Gilles; Arcambal, Angelique; Begue, Mickael; Maillot, Olivier; Sayah, Rima; Castanet, Romain; Caboche, Raoul; Liberati, Pedro; Slaoui, Hakim; Bouaziz, Medi; Borson, Olivier; et al. (Frontiers in Oncology, 2024)
Introduction: Prostate cancer is the fourth most commonly diagnosed cancer among men worldwide.Various tools are used to manage disease such as conventional radiotherapy. However, it has been demonstrated that large prostate volumes were often associated with higher rates of genitourinary and gastrointestinal toxicities. Currently, the improvements in radiotherapy technology have led to the development of stereotactic body radiotherapy, which delivers higher and much more accurate radiation doses. In order to complete literature data about short-term outcome and short-term toxic effects of stereotactic body radiotherapy, we aimed to share our experience about gastrointestinal and genitourinary toxicities associated with stereotactic body radiotherapy in prostate cancer in patients over 70 years old.We retrospectively reviewed the medical records of elderly patients with prostate cancer treated between 2021 and 2022. The elderly patients were treated with a non-coplanar robotic stereotactic body radiotherapy platform using real-time tracking of implanted fiducials. The prostate, with or without part of the seminal vesicles, was treated with a total dose of 36.25 Gy delivered in five fractions, each fraction being administered every other day.We analyzed a total of 80 elderly patients, comprising 38 low-, 37 intermediate-and 5 high-risk patients. The median follow-up duration was 12 months. We did not observe biochemical/clinical recurrence, distant metastasis, or death. Grade 2 acute genitourinary toxicity was observed in 9 patients (11.25%) and Grade 2 acute gastrointestinal toxicity in 4 patients (5.0%). We did not observe any grade 3 or more acute or late toxicities.Over the follow-up period, we noted a low frequency of gastrointestinal and genitourinary toxicities induced by stereotactic body radiotherapy in the context of prostate cancer in elderly patients.Therefore, stereotactic body radiotherapy seems to represent a promising treatment option for elderly patients, with acceptable acute toxicity.